Health information sharing on Facebook: An exploratory study on diabetes mellitus - Zainab A. AlQarni; Faisel Yunus; Mowafa S. Househ (Elsevier, 2016)
Summary: Background: Increasingly, people are using Facebook (FB) to share health information. However, little is known about the type of information sharing and its potential health consequences in the Arabic speaking world. This study attempts to fill this knowledge gap for diabetes mellitus (DM). Method: We conducted a retrospective qualitative FB content analysis using predefined eligibility criteria. The analysis was restricted to diabetes related groups in the Arabic speaking world. The data were collected between June 2010 and December 2015. A total of 55 groups were screened of which seven met the eligibility criteria. Results: We found 6107 posts in Arabic related to DM of which 1551 posts were included for further analysis. There were 458 (30%) FB posts from Egypt with no posts from Somalia, Yemen, Comoros, and Djibouti. The majority of the posts, 863 (56%), were from females. The focus of the posts was on sharing personal experiences (n = 423, 27%), raising awareness (n = 210, 3.5%), providing spiritual support (n = 162, 10.4%), sharing latest research (n = 147, 9.5%), and providing education (n = 110, 7.1%) on DM. A large number of the posts by people in 40-60 year age group were around finding out diagnosis related information due to limited access to care in their home countries. Conclusion: Patients with DM are increasingly sharing their health information with other FB users. This study will help inform future research with regard to health information sharing and designing appropriate interventions to harness the power of social media in improving public health. Keywords: Health information, Facebook, Diabetes mellitus, Arab world